Alternative mechanisms of labour market regulations - Izabela Ostoj (Ekonomia i Prawo, 2009)
An institutional order of labour market, according to new institutional economics, consists of formal and informal institutions. An idea of labour market deregulation refers to a number and a degree of restrictions of formal regulations of labour relations. A proposition can be put forward that labour market deregulation can be successful, if it is accompanied with adequate informal institutions. This article presents several examples of informal or only partly formalized mechanisms, such as: negotiations, mutuality as a rule, mediations and good practices. They can partly replace formal regulations of labour market and support the deregulation process.